The influences of the AMO and NAO on the sedimentary infill in an Azores Archipelago lake since ca. 1350 CE - Hernández, Armand; Rull, Valentí; Rubio de Inglés, Maria Jesús; Sánchez-López, Guiomar; Giralt, Santiago (Global and Planetary Change, 2017)
The location of the Azores Archipelago in the North Atlantic makes this group of islands an excellent setting to study the long-term behavior of large oceanic and atmospheric climate dynamic patterns, such as the Atlantic Multidecadal Oscillation (AMO) and the North Atlantic Oscillation (NAO). Here, we present the impacts of these patterns on Lake Empadadas (Azores Archipelago) from the Medieval Climate Anomaly (MCA) - Little Ice Age (LIA) transition to the present based on sedimentological, geochemical and biological characterizations of the sedimentary record. Multivariate analyses of a number of proxies including X-ray fluorescence (XRF), X-ray diffraction (XRD), total organic and inorganic carbon (TOC and TIC) and diatom life forms abundance reveal that the sedimentary infill evolution has been controlled by (i) fluctuations in the lake level and (ii) variations in organic matter accumulation. Both processes are governed by climate variability and modulated by anthropogenic activities associated with changes on the lake catchment. Changes in these two sedimentary processes have been used to infer five stages: (i) the MCA-LIA transition (ca. 1350–1450 CE) was characterized by a predominantly positive AMO phase, which led to intermediate lake levels and high organic matter concentration; (ii) the first half of the LIA (ca. 1450–1600 CE) was characterized by predominant lowstand conditions and intermediate organic matter deposition mainly related to negative AMO phases; (iii) the second half of the LIA (ca. 1600–1850 CE) was characterized by negative AMO and NAO phases, implying intermediate lake levels and high organic matter deposition; (iv) the Industrial era (ca. 1850–1980 CE) was characterized by the lowest lake level and organic matter accumulation associated with negative AMO phases; and (v) the period spanning between 1980 CE and the present reveals the highest lake levels and low organic matter deposition, being associated with very positive AMO conditions. At decadal-to-centennial scales, the ...